The Beauty of the Gods: Engagement with Laura Mark’s “Authenticating Hafu Identities on Instagram" - Schiff, Brian (Narrative Works, 2025)
I would like to begin by thanking Laura Mark (2025) for her thoughtful and provocative research on hafugods—an Instagram account for persons claiming half-Japanese identities. In her article, Mark convincingly employs the frame of small stories research in order to examine the interactional dynamics of moderating, bio-posting, commenting, and liking on hafugods.